Pemberdayaan Masyarakat Pemula UMKM Mie Basah Kelurahan Paccerakkang Kota Makassar Melalui Digitalisasi - Bachtiar, Irmah Halimah; Gafur, Gafur; Supiati, Supiati; Bachtiar, Ayu Darmawan; Hasan, Azizah (STMIK Royal, 2023)
The magnitude of the role of MSMEs as the backbone of the national economy is evidenced from data from the Ministry of Cooperatives and Small and Medium Enterprises for 2022 that the number of MSMEs in South Sulawesi has experienced a significant increase and in 2022 it will reach 268,299 units. However, this condition contrasts with Mr. Rahman Robin's MSMEs Mie Basah Manga Tiga, which does not provide optimal results, and sales sometimes experience a decline. The purpose of this service is to develop the Mangga Tiga wet noodle business through digital utilization. One of the government's newest programs in supporting MSME growth is